The Deconstruction of Traditional Scientific Paradigm of Ethnography in the Postmodern Anthropology - Klumbytė, Neringa (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to discuss the historical development of anthropology and to analyze the relationship between the postmodern and modern paradigms of ethnographic study. The author grounds the analysis on a view of postmodern ethnography as a deconstruction of the earlier studies and suggests a notion of creative imagination for understanding the changes in anthropology. The author argues that the postmodern ethnographic study is best understood as experemintal, both scientific and non-scienific practice that transgresses the modern distinctions of genres and disciplines.